Research on Decision-Making Strategies of Regional Geography Teaching in High School Based on Data-Driven - Yuan, Rui; Gao, Yaqi; Li, Jiansheng (Universitas Islam Indonesia, 2023)
With the development of big data technology, it has become a trend to analyze students’ behavioral data to promote teachers’ precision teaching. In this context, this study cooperates with a senior high school geography teacher in Changsha City, Hunan Province, collects the students’ examination data from 2020 to 2021 academic year with the help of Zhixue.com, divides the students into four groups according to the examination results, and takes regional geography knowledge as an example to analyze the weak knowledge points, discipline core literacy and practical application ability of students at all levels. Based on the analysis results, the improvement strategies of teachers’ subsequent precision teaching were proposed, including students’ stratification should be carried out according to daily performance and examination results; The weak knowledge points of students of different grades overlap and differ, so teachers should carry out targeted teaching for students of different grades. At the same time, the multi-level teaching method should be improved to enhance students’ discipline core literacy. Pay attention to contact life reality, enhance students’ practical application ability.